Mycorrhiza-induced changes in root growth and nutrient absorption of tea plants - SHAO, Ya-Dong; ZHANG, De-Jian; HU, Xian-Chun; WU, Qiang-Sheng; JIANG, Chang-Jun; XIA, Ting-Jun; GAO, Xiu-Bing; KUČA, Kamil (Plant, soil and environment, 2018)
Tea plants grown in acidic soils are strongly dependent on arbuscular mycorrhizas, whereas it is not clear whether soil arbuscular mycorrhizal fungi (AMF) improve plant growth, root development, and nutrient absorption in tea plants. A potted study was conducted to determine the effects of Claroideoglomus etunicatum, Diversispora spurca, D. versiformis and a mixture of the three AMF species on plant growth, root morphology, root-hair growth, and leaf nutrient status in Camellia sinensis cv. Fuding Dabaicha in Jingzhou, China. After 12 weeks of AMF inoculation, root mycorrhizal colonization ranged from 15.12% to 40.23%. AMF inoculation heavily increased plant height, shoot and root biomass, and total leaf area, whilst the increased effect was ranked as C. etunicatum > D. spurca > mixed-AMF > D. versiformis in the decreasing order. Mycorrhizal inoculation also considerably increased total root length and volume, whereas obviously inhibited root-hair length and number, in company with an increment in root-hair diameter. Leaf N, P, K, Ca, Mg, Zn, and Mn contents were significantly higher in AMF-inoculated plants than in non-AMF-inoculated plants, regardless of AMF species. It concludes that AMF inoculation had positive effects on plant growth performance, root morphology, and leaf nutrient levels in cv. Fuding Dabaicha seedlings, whilst C. etunicatum performed the best effects.